2018
DOI: 10.1038/s41467-018-06359-y
|View full text |Cite
|
Sign up to set email alerts
|

Sounding-rocket microgravity experiments on alumina dust

Abstract: Alumina (Al2O3) is believed to be the first major condensate to form in the gas outflow from oxygen-rich evolved stars because of the refractoriness and that α-Al2O3 (corundum, most stable polymorph) is a potential origin of a 13 μm feature that appears close to stars. However, no one has directly reproduced the 13 μm feature experimentally, and it has remained as a noteworthy unidentified infrared band. Here, we report nucleation experiments on Al2O3 nanoparticles monitored by a specially designed infrared sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…crystal structures) of alumina have been suggested (Sargent 2019). A recently conducted microgravity experiment in a sounding-rocket has shown that solid Al 2 O 3 exhibits broad emission in the 11−12 µm wavelength range (Ishizuka et al 2018). Other dust features often seen in oxygenrich AGB stars are located at around 10 µm and 18 µm and they are attributed to Si−O streching and Si−O−Si bending modes, respectively (Hackwell et al 1970).…”
Section: Introductionmentioning
confidence: 99%
“…crystal structures) of alumina have been suggested (Sargent 2019). A recently conducted microgravity experiment in a sounding-rocket has shown that solid Al 2 O 3 exhibits broad emission in the 11−12 µm wavelength range (Ishizuka et al 2018). Other dust features often seen in oxygenrich AGB stars are located at around 10 µm and 18 µm and they are attributed to Si−O streching and Si−O−Si bending modes, respectively (Hackwell et al 1970).…”
Section: Introductionmentioning
confidence: 99%
“…We recently succeeded in reproducing the small fwhm of the astronomical 13 μm band in experiments under μG environment . Then, we found that the peak wavelength was shifted toward longer wavelength (smaller wavenumber) compared to the astronomical 13 μm band, which was attributed to growing anisotropy of aluminum oxide nanoparticles . Although the degree of anisotropy may be different, the new pathway will be available in both the previous under μG experiment and astronomical environments.…”
Section: Discussionmentioning
confidence: 90%
“…Describing clusters growth remains a vivid and challenging subject for laboratory cluster sources and nanoparticles production, but also atmospheric aerosol, cosmic dust, , and combustion. , Because of their tiny size, clusters cannot be described within a condensed matter concept, and classical nucleation theory (CNT) fails to explain their growth . Indeed, CNT remains controversial regarding quantitative results, and its conceptual limitations have been raised by several authors. , As an alternative to CNT which assumes that the seed is homogeneous and isostructural to the bulk crystal, the Ostwald rule states that the first growing phase is not always the most stable in bulk.…”
Section: Introductionmentioning
confidence: 99%
“…Describing clusters growth remains a vivid and challenging subject for laboratory cluster sources and nanoparticles production, 1 but also atmospheric aerosol, 2−7 cosmic dust, 8,9 and combustion. 10,11 Because of their tiny size, clusters cannot be described within a condensed matter concept, and classical nucleation theory (CNT) fails to explain their growth.…”
Section: ■ Introductionmentioning
confidence: 99%